Permasalahan Perkembangan Bahasa Baku Yang Dihadapi Anak Usia Dini dan Faktor-Faktornya di Komplek Medan Estatet - Nabillah Ghassani; Hasraini Waruwu; Nazwa Suhana; Muhammad Aryo; Gymnestie Utami; Fitra Audina (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Early childhood development is something that will disrupt a child's life, which arises from a mismatch in their development. The research objective of this research is to understand the problems faced by young children, minimize the emergence and impact of these problems, and be able to provide appropriate assistance efforts. Therefore, it is important to know about early childhood development because at this time, children are in a golden age that only comes once and cannot be repeated. As educators and parents, it is mandatory to see children's growth and development from an early age, and what a loss it is for parents who don't care about their children's development. A child's problem is something that is disturbing. Language development disorders are the inability or limitations in using linguistic symbols to communicate verbally or delays in a child's ability to develop speech and language according to their age group, gender, customs and intelligence. Therefore, if speech and language disorders are not treated appropriately, there will be problems with reading ability, verbal ability, behavior, psychosocial adjustment and poor academic ability. Parents/teachers need to understand this problematic behavior because